Basal insulin peglispro increases lipid oxidation, metabolic flexibility, thermogenesis and ketone bodies compared to insulin glargine in subjects with type 1 diabetes mellitus. Issue 5 (4th February 2018) - Porksen, Niels K.; Linnebjerg, Helle; Lam, Eric Chen Quin; Garhyan, Parag; Pachori, Alok; Pratley, Richard E.; Smith, Steven R.
Abstract : Aims: When treated with basal insulin peglispro (BIL), patients with type 1 diabetes mellitus (T1DM) exhibit weight loss and lower prandial insulin requirements versus insulin glargine (GL), while total insulin requirements remain similar. One possible explanation is enhanced lipid oxidation and improved ability to switch between glucose and lipid metabolism with BIL. This study compared the effects of BIL and GL on glucose and lipid metabolism in subjects with T1DM. Materials and Methods: Fifteen subjects with T1DM were enrolled into this open‐label, randomised, crossover study, and received once‐daily stable, individualised, subcutaneous doses of BIL and GL for 4 weeks each. Respiratory quotient (RQ) was measured using whole‐room calorimetry, and energy expenditure (EE) and concentrations of ketone bodies (3‐hydroxybutyrate) and acylcarnitines were assessed. Results: Mean sleep RQ was lower during the BIL (0.822) than the GL (0.846) treatment period, indicating greater lipid metabolism during the post‐absorptive period with BIL. Increases in carbohydrate oxidation following breakfast were greater during BIL than GL treatment (mean change in RQ following breakfast 0.111 for BIL, 0.063 for GL). Furthermore, BIL treatment increased total daily EE versus GL (2215.9 kcal/d for BIL, 2135.5 kcal/d for GL). Concentrations of ketone bodies and acylcarnitines appeared to be higher following BIL than GL treatment. Conclusions: BIL increased sleeping fat oxidation, EE, ketone bodies, acylcarnitines and post‐prandial glucose metabolism when switching from conventional insulin, thus, restoring metabolic flexibility and increasing thermogenesis. These changes may explain the previously observed weight loss with BIL versus GL.